Affirmative Critique as Minor Qualitative Critical Inquiry: A Storying of a Becoming Critical Engagement with What Happens. Issue 4 (December 2017) - Andersen, Camilla Eline
This article considers what to do with a political questioning of how to perform qualitative research when engaging with stuck bodily happenings. It does so inspired by philosophical-theoretical-methodological flows in the field of qualitative research where working against colonial ways of knowing and justice-oriented knowledge creation is of importance. The article's storying evolves from a reality- and philosophy-driven curiosity of race in relation to professionalism in early childhood education in a Nordic landscape. As a way of thinking through how to perform critical qualitative inquiry when positioned in a monist materialist thinking and within a philosophy of desire (Deleuze & Guattari, 1983, 1987), it explores Braidotti's (2011, 2013) "affirmative critique" as a way of working creatively with resistance.